The Expression of Emotions in Ancient Egypt and Mesopotamia - Hsu, Shih-Wei,; Raduà, Jaume Llop, (Culture and History of the Ancient Near East ;, 2021)
The volume The Expression of Emotions in Ancient Egypt and Mesopotamia offers an overview of the study of emotions in ancient texts, discusses the concept of emotions in Ancient Egypt and Mesopotamia, and shows how emotions are described in the ancient texts. In the section dedicated to Ancient Egypt, scholars discuss emotions such as fear, depression, anger, feelings of pain, envy, jealousy and greed, with evidence from different text genres, as well as emotions from the Late Ramesside Letters and royal inscriptions. In the section dedicated to Ancient Mesopotamia, scholars present a wide range of perspectives on Sumerian and Akkadian literary and archival texts that treat emotions in different periods.